2015
DOI: 10.1111/jth.13164
|View full text |Cite
|
Sign up to set email alerts
|

Bemiparin for thromboprophylaxis after benign gynecologic surgery: a randomized clinical trial

Abstract: To cite this article: Alalaf SK, Jawad AK, Jawad RK, Ali MS, Al Tawil NG. Bemiparin for thromboprophylaxis after benign gynecologic surgery: a randomized clinical trial. J Thromb Haemost 2015; 13: 2161-7.Summary. Background: Venous thromboembolism (VTE) is the leading cause of mortality and morbidity in women following gynecologic surgery. Objectives: To determine the efficacy of a second-generation low molecular weight heparin (bemiparin) for thromboprophylaxis after benign gynecologic surgery. Methods: We pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Dalteparin is used at doses of either 2500 units or 5000 units daily. Several small trials are evaluating the use of newer agents, such as bemiparin [45].…”
Section: Pharmacologic Thromboprophylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…Dalteparin is used at doses of either 2500 units or 5000 units daily. Several small trials are evaluating the use of newer agents, such as bemiparin [45].…”
Section: Pharmacologic Thromboprophylaxismentioning
confidence: 99%
“…Benefits. Use of perioperative pharmacologic prophylaxis has been shown to decrease the risk of VTE in both the general population and among gynecologic surgery patients [45]. A systematic review of patients undergoing gynecologic surgery for cancer showed that preoperative use of heparin decreased risk of DVT (relative risk, .58; 95% CI, .38−2.17) [46].…”
Section: Pharmacologic Thromboprophylaxismentioning
confidence: 99%